Approximation of holomorphic functions by Taylor-Abel-Poisson means - Savchuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We investigate approximations of functions $f$ holomorphic in the unit disk by means $A_{ρ, r}(f)$ for $ρ → 1_-$. In terms of an error of the approximation by these means, the constructive characteristic of classes of holomorphic functions $H_p^r \text{\;Lip\,}α$ is given. The problem of the saturation of $A_{ρ, r}(f)$ in the Hardy space $H_p$ is solved.